(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study examines the use of Qur’anic verses, Prophet hadiths, and Arabic words in the logos of ministries, authorities, and universities in Pakistan as a manifestation of the country’s Islamic and cultural identity. The research aims to document the presence of these texts in institutional logos, analyze their semantic relevance to the functions and missions of the respective institutions, and measure the level of public awareness and understanding of their meanings. The study adopts a descriptive-analytical approach and employs a questionnaire distributed to a sample of 420 participants representing three main groups: the general public, the government sector, and the educational sector. The findings reveal that the incorporation of Qur’anic and Arabic expressions in institutional logos is widespread and often closely aligned with institutional functions—judicial bodies emphasize justice and integrity, educational institutions highlight knowledge and reflection, while medical and agricultural institutions reference healing and sustenance. Results indicate that approximately 60% of respondents are aware of the presence of Qur’anic verses or Arabic expressions in institutional logos. However, only 39% report understanding their meanings or translations, revealing a gap between symbolic recognition and semantic comprehension. Notably, the general public demonstrated the lowest level of understanding, with only 12% reporting knowledge of the meanings, reflecting a significant deficiency in semantic awareness. The study recommends strengthening linguistic and cultural awareness to ensure that the symbolic use of Arabic texts in institutional logos is accompanied by meaningful understanding.